2009
DOI: 10.1177/0887302x08327087
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Examination of Women’s Fashion and Beauty Magazine Advertisements in the United States and South Korea

Abstract: To compare differences in the construction of women's images across the United States and South Korea, this study examines advertisements in fashion and beauty magazines of the two countries. The content analysis includes product/service types, models' characteristics, and the degrees of female objectification in this advertising venue. More body-related than non-bodyrelated product ads are prevalent in magazines from both countries, yet Korean magazines feature more body-related ads than those in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 27 publications
6
40
0
Order By: Relevance
“…For example, researchers have suggested that beauty for Korean women is constructed from facial attributes rather than the body, while the reverse appears to be true for U.S. women (Frith, Shaw, & Cheng, 2005;Jung & Lee, 2009). Namely, Korean women reported engaging in cosmetic procedures followed by extreme dieting as compared to U.S. women who reported engaging in the use of diet aids followed by extreme dieting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers have suggested that beauty for Korean women is constructed from facial attributes rather than the body, while the reverse appears to be true for U.S. women (Frith, Shaw, & Cheng, 2005;Jung & Lee, 2009). Namely, Korean women reported engaging in cosmetic procedures followed by extreme dieting as compared to U.S. women who reported engaging in the use of diet aids followed by extreme dieting.…”
Section: Discussionmentioning
confidence: 99%
“…The body ideal promoted for women in Western cultures is unrealistically thin and increasingly "sexy." About one-half of advertisements in a variety of magazines were found to depict women as sex objects (Stankiewicz and Rosselli 2008), and the sexualization of women in advertisements increased significantly between 1983 and 2003 (Reichert and Carpenter 2004). Peter and Valkenburg (2007) concluded that there is increased sexual content in the media, particularly with the advent of the internet.…”
Section: Sexual Objectification Of Womenmentioning
confidence: 97%
“…Further, the women in the advertising images look S.Y. Bae et al 242 perfect and absolutely beautiful, which indicates the role of the media in idealizing beauty and maximizing attractiveness (Jung & Lee, 2009). D&G portrays the woman as a provocative housewife who spends money on beautifying herself to represent an object provoking sensual thoughts in her husband.…”
Section: Perceptions Of Sexual Versus Non-sexual Appeals In Advertisementioning
confidence: 97%
“…Even though this figure represented fecundity and was shown as a decorative element, a sexual object, and dependent on men, D&G Facebook visitors appeared not to consciously notice the stereotyped images of women portrayed in the ads. Further, the women in these advertising images reflected idealized beauty to maximize attraction (Jung & Lee, 2009). Most of the Facebook visitors evaluated the models and products.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 97%
See 1 more Smart Citation